2010
DOI: 10.1111/j.1365-2753.2009.01212.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported drug allergies and the diagnostic work‐up in the surgical population

Abstract: Objective The diagnostic work-up of a drug hypersensitivity reaction is indeed difficult. In general, medical documentation of allergic reactions in medical reports is usually highly deficient or non-existent. The aim of this study was to analyse the prevalence of selfreported drug allergies in the surgical population as well as the criteria used in the diagnosis of drug hypersensitivity reactions. Methods A prospective study with the consecutive participation of 1439 patients, following surgical intervention,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…[15][16][17] Drug allergies were most commonly reported to antibiotics, NSAIDs and opioids and were more common in older, female patients. These findings are in keeping with previous studies [8][9][10][11][12][13][14] but the reasons for them are unknown. One possibility is that older patients have had a greater number of potentially sensitising drug exposures, with antibiotics and analgesics some of the most frequently used drugs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[15][16][17] Drug allergies were most commonly reported to antibiotics, NSAIDs and opioids and were more common in older, female patients. These findings are in keeping with previous studies [8][9][10][11][12][13][14] but the reasons for them are unknown. One possibility is that older patients have had a greater number of potentially sensitising drug exposures, with antibiotics and analgesics some of the most frequently used drugs.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies suggest a prevalence ranging from 7-38%, with antibiotics, non-steroidal anti-inflammatories (NSAIDs) and opioids the most frequently reported culprits. [8][9][10][11][12][13][14] It is widely accepted that a significant proportion of drug allergy labels are incorrect, with side effects or other non-allergic phenomena misattributed to allergy by patients or their healthcare providers. [15][16][17] We aimed to determine the prevalence of patient-reported drug allergies in the UK elective surgical population and risk stratify the reported reactions for likelihood of genuine allergy.…”
Section: Introductionmentioning
confidence: 99%
“…Similar or even lower rates are reported by numerous other publications. 26,27,28,29 In our opinion, GPs do not consider the immediate impact of using second line therapies (efficacy, adverse effects, antibiotic resistances), and more importantly do not perceive the need for long term clinical decisions.…”
Section: F O R P U B L I C a T I O Nmentioning
confidence: 99%
“…Depending on study population, definition of drug allergy and other factors, the reported incidence has been between 7,8% (in general population) and 39% (in surgical population). 13,14,15 Unfortunatelly, the proportion of patients who underwent further investigation following the adverse reaction is less than 30-50% and it has been shown that between 40-50% of them are confirmed as being allergic. 16 Patients with self-reported allergies most commonly considered themselves allergic to antibiotics (more than 40% to penicillins and other βlactams), NSAIDs, opioids, iodine, diuretics, etc.…”
Section: Epidemiologymentioning
confidence: 99%